Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

2nd International Conference on Progressive Multifocal Leukoencephalopathy (PML) 2015: JCV virology, progressive multifocal leukoencephalopathy pathogenesis, diagnosis and risk stratification, and new approaches to prevention and treatment - Andriani C. Patera; Scott L. Butler; Paola Cinque; David B. Clifford; Robert Elston; Robert L. Garcea; Eugene O. Major; Dejan Pavlovic; Ilse S. Peterson; Anne M. Ryan; Kenneth L. Tyler; Thomas Weber (Journal of NeuroVirology, 2015)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

Current and elevated levels of UV‐B radiation have few impacts on yields of perennial forage crops - Yousef A. Papadopoulos; Robert J. Gordon; Kenneth B. Mcrae; RoY. S. Bush; Gilles Bélanger; E. AnnE. Butler; Sherry A. E. Fillmore; Malcolm Morrison (Global Change Biology, 1999)
Summary Two experiments assessed the effect of current and elevated levels of ultraviolet B (UV‐B) radiation on forage crop production. The effect of current levels of UV‐B radiation was assessed by comparing the growth of eight cultivars of four legume and four grass species for three growing seasons (1994–96) under simulated sward conditions in the field. An exclusion system using cellulose diacetate or polyester covers provided comparable growing conditions for the plants, except for the presence or absence of ambient UV‐B radiation, respectively. The second experiment studied the effect of elevated levels of UV‐B on eight cultivars of two legume and two grass species in the greenhouse under simulated sward conditions. Natural lighting with sufficient supplemental light was used to provide ideal growing conditions for a 16‐h day length. Separate sets of UV lights were installed to provide UV‐B levels at approximately the same intensity as would be found in mid summer, and 33% and 66% more than this value. A fourth treatment consisted of removing UV‐B radiation by using a polyester filter. Plant production was measured in both experiments. In 1994, field herbage yields from all young grass and legume seedlings were not significantly affected by the exclusion of ambient UV‐B radiation, with the exception of alfalfa. Intra‐specific variations with alfalfa yields were found for reduced levels of UV‐B radiation. In general, these trends persisted as stands matured during two post seeding years. In the second experiment, no significant differences were observed for all tested species with increasing levels of UV‐B radiation, except with some alfalfa cultivars and one birdsfoot trefoil cultivar. Collectively, these results demonstrate that in the northern latitudes young and mature plants of the studied species are resistant to current and potentially higher levels of solar UV‐B radiation, with the exception of some alfalfa cultivars. The yield of these cultivars increased under enhanced levels of UV‐B radiation in the greenhouse and decreased when UV‐B was excluded in the field.

On the mechanism of action of thiamin enzymes, Crystal structure of 2-(α-hydroxyethyl)thiamin pyrophosphate (HETPP). Complexes of HETPP with zinc(II) and cadmium(II) - Gerasimos Malandrinos; Maria Louloudi; Cristiana A. Mitsopoulou; Ian S. Butler; Robert Bau; N. Hadjiliadis (JBIC Journal of Biological Inorganic Chemistry, 1998)

Conservation Genetics of North American Freshwater Mussels Amblema and Megalonaias - Margaret Mulvey; Charles Lydeard; Debra L. Pyer; Kimberly M. Hicks; Jayne Brim‐Box; James D. Williams; Robert S. Butler (Conservation Biology, 1997)
Freshwater bivalves are among the most endangered groups of organisms in North America. Efforts to protect the declining mussel fauna are confounded by ambiguities associated with recognition of distinct evolutionary entities or species. This, in part, is due to the paucity of reliable morphological characters for differentiating taxa. We have employed allozymes and DNA sequence data to search for diagnosably distinct evolutionary entities within two problematic genera of unionid mussels, Amblema and Megalonaias. Within the genus Amblema three species are recognized based on our DNA sequence data for the mitochondrial 16S rRNA and allozyme data (Amblema neislerii, A. plicata, and A. elliotti). Only one taxonomically distinct entity is recognized within the genus Megalonaias—M. nervosa. Megalonaias boykiniana of the Apalachicolan Region is not diagnosable and does not warrant specific taxonomic status. Interestingly, Megalonaias from west of the Mississippi River, including the Mississippi, exhibited an allozyme and mtDNA haplotype frequency shift suggestive of an east‐west dichotomy. The results of this study eliminate one subspecies of Amblema and increase the range of A. plicata. This should not affect the conservation status of “currently stable” assigned to A. plicata by Williams et al. (1993). The conservation status of A. elliotti needs to be reexamined because its distribution appears to be limited to the Coosa River System in Alabama and Georgia.

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)